2018
DOI: 10.1177/2056305118772836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sampling Methods for Content Analysis of Twitter Data

Abstract: Despite the existing evaluation of the sampling options for periodical media content, only a few empirical studies have examined whether probability sampling methods can be applicable to social media content other than simple random sampling. This article tests the efficiency of simple random sampling and constructed week sampling, by varying the sample size of Twitter content related to the 2014 South Carolina gubernatorial election. We examine how many weeks were needed to adequately represent 5 months of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…From the 185,258 tweets collected, a random sample for classification of 1,200 tweets (300 tweets for each keyword) was selected using Excel's random number generator. Although there were significant differences in the total number of tweets extracted for each keyword, equal sample sizes (Kim et al , 2018) were selected to give a balanced set. This maximises the reliability of comparisons between keyword groups.…”
Section: Methodsmentioning
confidence: 99%
“…From the 185,258 tweets collected, a random sample for classification of 1,200 tweets (300 tweets for each keyword) was selected using Excel's random number generator. Although there were significant differences in the total number of tweets extracted for each keyword, equal sample sizes (Kim et al , 2018) were selected to give a balanced set. This maximises the reliability of comparisons between keyword groups.…”
Section: Methodsmentioning
confidence: 99%
“…Population was all the students of Sport Coaching Education and the sample was taken by total sampling (Sharma, 2017). Data collection using questionnaire and technique tests (physical condition).To assess the evaluation of gymnastic basic skills the research used the model of Kim, Jang, Kim, & Wan, (2018). Data analysis using Independent sample t-Test and correlation by SPSS Amos .23.…”
Section: Methodsmentioning
confidence: 99%
“…This technique involves media content based on the day and week. Studies have shown that weekly built-in sampling can reduce the possibility of overestimating or underestimating certain days of the week (Hwalbin Kim et al, 2018).…”
Section: Methodsmentioning
confidence: 99%